CRITERION-BASED ASSESSMENT OF STUDENTS' ACADEMIC ACHIEVEMENTS IN RUSSIAN LANGUAGE (Spectrum Journal of Innovation, Reforms and Development, 2024)
This scientific article is devoted to the criterion-based assessment of students' learning achievements in Russian language. The main problems of traditional assessment methods are considered and the necessity of using the criterion-based approach is justified. The developed evaluation criteria describing grammar, vocabulary and argumentation are presented, and examples of achievement levels are given. The application of criterion-based assessment allows to evaluate the level of students' language skills more objectively and completely and to develop an individualized approach in teaching Russian language.